Indices to debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town, 1971)
South Africa Parliament House of Assembly. Debates of the House of Assembly (Hansard).
Merged with: Debates of the House of Delegates, and Debates of the House of Representatives, to form: Debates of Parliament. Debates of Standing Committees. 139 v. 22 cm.
Keywords: Indices to debates; House of Assembly; Hansard; Second Session - Fourth Parliament; January; June; 1971; vol. 36; Index to speeches; Index to questions